2020
DOI: 10.1016/j.msard.2020.102463
|View full text |Cite
|
Sign up to set email alerts
|

NFL and CXCL13 may reveal disease activity in clinically and radiologically stable MS

Abstract: Running title: NFL and CXCL13 may reveal disease activity in clinically and radiologically stable MS Disclosure of Conflict of Interest statement AS reports no conflicts of interests. CM has received honoraria for lectures and advisory boards from Biogen, Merck Novartis, Roche and Sanofi. HZ has served at scientific advisory boards for Denali, Roche Diagnostics, Wave, Samumed and CogRx, has given lectures in symposia sponsored by Fujirebio, Alzecure and Biogen, and is a co-founder of Brain Biomarker Solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…We confirmed that high NFL levels are good predictors of patients not fulfilling NEDA-3. 10 In line with the results of a previous study, 31 other measures of disease activity. We found, however, that a significant proportion of patients with ON had normal cNFL levels at diagnosis and no evidence of ongoing disease activity on MRI.…”
Section: Discussionsupporting
confidence: 85%
“…We confirmed that high NFL levels are good predictors of patients not fulfilling NEDA-3. 10 In line with the results of a previous study, 31 other measures of disease activity. We found, however, that a significant proportion of patients with ON had normal cNFL levels at diagnosis and no evidence of ongoing disease activity on MRI.…”
Section: Discussionsupporting
confidence: 85%
“…Patients with high sNfL had numerically accelerated brain volume loss in the preceding and following year. If our findings will be supported in future research, 15 sNfL may also qualify as an indirect marker of contemporary neurodegeneration that is not captured by the present NEDA-3 concept. Compared to direct assessment of brain volume loss by MRI volumetric methods, as conceptualized in the NEDA-4, 7 an sNfL monitoring may offer an advantage of higher accuracy and precision, detection of changes in entire neuroaxis, greater potential for standardization, and lower financial burden.…”
Section: Discussionmentioning
confidence: 67%
“…An increasing number of studies has established sNfL as marker of disease activity, drug response, and prediction of the disease course, both on clinical and MRI grounds. 9 19 However, the practical value of sNfL as a monitoring tool for clinical practice has been less studied. 13 20…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of CSF cytokines has also demonstrated an increase in CXCL13 in patients with PPMS compared to healthy control ( 90 ). Additionally, in patients with PPMS, CSF CXCL13 was found to correlate with CSF B and T cell levels ( 91 ) and higher amounts of CXCL13 were found in patients with disease activity compared to those without ( 92 ). Overall, these data suggest a possible pathogenic role for B cells in PPMS via LT-α and CXCL13, which may be mitigated by anti-CD20 therapies.…”
Section: Mechanism Of Action Of B Cell Mediated Disease Progression In Ppmsmentioning
confidence: 99%